Kenya’s Constitutional Amendments, Referendum Questions and Promoters of Popular Initiatives: Lessons from Lithuania - Mwakuni, Leonard Muye (Teisė, 2025)
The Constitution of Kenya, 2010 dedicates Chapter sixteen to its amendment through parliamentary and popular initiatives. The Kenyan experience shows that there have been several proposed constitutional amendments to the 2010 Constitution since 2013 through both parliamentary and popular initiatives that have all been unsuccessful. Several issues have arisen concerning constitutional amendments such as the nature and scope of national referendum questions and whether State actors can initiate popular initiative amendments. In certain instances, the superior courts have had the opportunity to pronounce themselves on these issues through constitutional interpretation of the amendment provisions and determining the constitutionality of the amendment processes and Bills. This article critically analyses the amendment of the 2010 Constitution, the nature and scope of national referendum questions, and whether State actors can initiate popular initiative amendments. This article benefits from the comparative jurisprudence from Lithuania, especially on the nature and scope of national referendum questions, and uses the purposive approach of interpreting the constitutional amendment provisions using the emerging jurisprudence emerging from the superior courts, comparative jurisprudence and scholarly literature.